2009
DOI: 10.1158/1078-0432.ccr-09-1493
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Potential of Angiogenic Growth Factors and Circulating Endothelial Cells in Breast Cancer Patients Receiving Metronomic Chemotherapy Plus Bevacizumab

Abstract: Purpose: The association of chemotherapy and antiangiogenic drugs has shown efficacy in clinical oncology. However, there is a need for biomarkers that allow selection of patients who are likely to benefit from such treatment and are useful for indicating best drug combination and schedule. Experimental Design: We investigated the predictive potential of six angiogenic molecules/transcripts and nine subpopulations of circulating endothelial cells (CEC) and progenitors (CEP) in 46 patients with advanced breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 23 publications
1
61
3
3
Order By: Relevance
“…Higher baseline CEC was correlated with delayed disease progression in patients with non-small cell lung and breast cancer (29,30). We did not find a correlation between baseline CEC numbers and therapeutic effect, however significant correlations between baseline levels of SDF1, c-kit(þ) CEP number and c-kit(þ) ratio in CEC were shown with E7080 treatment duration.…”
Section: Discussioncontrasting
confidence: 68%
“…Higher baseline CEC was correlated with delayed disease progression in patients with non-small cell lung and breast cancer (29,30). We did not find a correlation between baseline CEC numbers and therapeutic effect, however significant correlations between baseline levels of SDF1, c-kit(þ) CEP number and c-kit(þ) ratio in CEC were shown with E7080 treatment duration.…”
Section: Discussioncontrasting
confidence: 68%
“…The utility of plasma or serum VEGF levels as a prognostic or predictive biomarker in oncology has been inconsistent in the literature. [21][22][23] This is probably secondary to the difficulties in accurately measuring tumor released or associated VEGF as recent data suggest that plasma or serum measurements of VEGF are highly dependent on platelet count and phlebotomy technique. 19,20 Thus, our results with urine VEGF and plasma VCAM may be more relevant clinically, precisely because we have chosen to study a more robust, and therefore predictive, marker of in vivo VEGF effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of surrogate biomarkers able to define their optimal biological dosage (OBD), and/or to predict the clinical benefit in a given patient, and/or to predict patient's escape from the therapy is hampering their clinical development. 18 We and others [19][20][21][22][23][24][25][26][27][28][29] have recently reported that the measurement of CECs and CEPs in cancer patients receiving antiangiogenic drugs is a surrogate biomarker that has clinical predictive potential for patients' selection and follow-up. Using a flow cytometry approach similar to what we have developed and validated for CEC and CEP count, 13 we report here a protocol for PPC enumeration in the preclinical and clinical settings.…”
Section: Discussionmentioning
confidence: 99%